Porous alumina from protein foaming-consolidation method containing hydrothermal derived hydroxyapatited powder - Fadli, Ahmad; Sopyan, Iis; Ramesh, Singh (Trans Tech Publications Ltd., Switzerland, 2012)
Porous alumina containing hydrothermal derived hydroxyapatite (HA) composite were successfully fabricated via protein foaming-consolidation method. Alumina and HA powders were mixed with yolk, starch and darvan 821 A at an adjusted mass ratio to make slurry. The slurries were cast into cylindrical shaped molds and then dried for foaming and consolidation process. Subsequently, the dried bodies were burned at 600°C for 1 h, followed by sintering at temperatures of 1300 - 1400°C for 2 h. The porous alumina-HA composites with pore size in the range of 95-300 µm and density of 2.7 – 2.9 g cm-3 were obtained. Porosity of bodies decreased from 31.7 to 27.6% when sintering temperatures increased from 1300 to 1400°C. The increasing HA-to-alumina mass ratio from 0.2 to 0.8 w/w increased compressive strength of sintered bodies from 2.3 to 10.0 MPa. XRD pattern results show intensity of tricalcium phosphate (TCP) phase increased with sintering temperatures and also found that the sintering process did not alter phases in the porous bodies